Chemically reversible binding of H2S to a zinc porphyrin complex: towards implementation of a reversible sensor via a "coordinative-based approach". Issue 6 (19th January 2017) - Strianese, Maria; Lamberti, Marina; Pellecchia, Claudio
Abstract : By HR MALDI-FT-ICR and 1 H NMR experiments we provide evidence that HS − coordination occurs at the zinc centre. The zinc hydrosulfido adduct remained stable for a whole week, as assessed via NMR. Abstract : Binding of hydrogen sulfide (H2 S) to a zinc porphyrin complex and the stabilization of the related zinc hydrosulfido adduct are explored. High-resolution MALDI Fourier transform ion cyclotron resonance mass spectrometry (HR MALDI-FT-ICR) and 1 H NMR experiments provide evidence that HS − coordination occurs at the zinc centre. The coordination of HS − occurs in a reversible manner and modulates fluorescence emission of a tetra( N -methylpyridyl)porphine zinc complex (TMPyPZn). The results highlight the potential of TMPyPZn and related systems for the implementation of fast and simple H2 S sensors via a coordinative-based approach.